Photography techniques with Adobe Photoshop CS5 learn by video - Grey, Tim; Aaland, Mikkel (Video2brain.com, 2010)
"This innovative product from Adobe Press combines an incredible 10 hours of high quality HD video instruction and a full-color printed reference to teach the fundamentals of Photoshop for Photographers, plus the latest features in CS5, as well as Camera RAW, image management in Bridge, masking, creating HDR images, making complex selections and color corrections, image retouching, and more. Adobe Certified Instructors Tim Grey and Mikkel Aaland present this video training with an easy-to-follow style that makes it fun to learn."--Resource description page.
Keywords: Adobe Photoshop; Photography -- Digital techniques; Photographie numérique; Photography; Digital techniques; Electronic videos